Teacher’s Strategies in Teaching English for Students of Hearing Disorder - Chairun Nisak; Iskandar Abdul Samad; Tgk. Maya Silviiyanti (Universitas Syiah Kuala, 2019)
Teaching English for the students of hearing disorder seems difficult to English teacher. The students need different kind of language treatment in learning and the teacher needs various strategies in teaching. This study aims to determine the application of strategies used by an English teacher for the students of hearing disorder and the challenges faced by the teacher in teaching at SMPLB YPAC Banda Aceh. The design of this study was descriptive qualitative research. It concerned on the strategies used by the teacher and the challenges faced by the teacher in implementing the strategies. The writer used observation sheet and guiding interview as the instruments. The data were presented in form of list and narration. Based on the results of research and discussion could be concluded the strategies used by the teacher were facilitative strategies, repair strategies and memory strategies. The difficulties faced by teacher in implementing the strategies were in communication, student’s limited ability to comprehend the material and applying grammar learning strategies. Facilitative and repair strategies are suggested to be applied in order to avoid and to fix communication breakdown. Memory strategies also could be used to help the students in memorizing and retrieving information.